Seeing is not seeing: κένωσις of the image (A. Tarkovsky), blind-seer (C. Monet, J.-L. Godard) and the remains of sacred blue - Gonzalo Carbó, Antoni (Escritura e Imagen, 2024)
«It is certainly not enough to see» (Jean-Luc Marion); «to see is to see nothing» (Michel de Certeau); «the blind can be a seer» (Jacques Derrida). The κένωσις (‘emptying’) of the image is very well expressed in the final sequence of the film Andrei Rubliov (1966, Andrei Tarkovsky), which records the passage from the image (the face of Christ the Redeemer), the visible, to the non-image (the empty white tablet) of the icon «disfigured» (Isaiah 52:14) by the rain, the invisible materialised in the remains of blue pigment. The blindness-clairvoyance contraposition is reflected in Marcel Proust’s expression, from Claude Monet, that Jean-Luc Godard introduces in his film Adieu au langage (2014): «to paint what is not seen … the insufficiency of the eye». The icon comes from the κένωσις of the image. The painter (Rubliov, Tarkovski) sees more than the visible, like the blind, painter and seer par excellence (Monet, Godard, Derek Jarman).
Keywords: theology of the icon; κένωσις of the image; blindness-clairvoyance; Marcel Proust; Jean-Luc Godard; Andréi Tarkovski; Derek Jarman; color blue